The Effects of Soil Strength And Slope Geometry Parameters On Slope Stability - Tan, Nian Han (2021)
Many slope failure incidents happened in Malaysia. One of the main causes of artificial slope failures was the inaccurate slope analysis due to the lack of understanding on the principles and factors affecting slope stability. In order to obtain an accurate prediction on the safety factor of slope (FS), correct slip surface prediction, proper soil strength and slope geometry parameters selection are essential. There are a lot of software programs available for slope stability analysis but excel spreadsheet is still commonly used in engineering practices as it is cheaper. The aim of this study was to study the factors affecting the slope stability. In this study, an Excel spreadsheet was developed for slope stability analysis using Simplified Bishop Method. Then, it was used to find the relationship between soil strength parameters and FS for the slope with a fixed surface of failure. Then, GEO5 software program was used to analyze minimum FS and determine the critical slip surface by applying different soil strength and slope geometry parameters. Lastly, results acquired were compared and discussed. It was found that with the increase of soil unit weight which acted as a driving force, the FS of slope decreased, the critical slip surface became larger and deeper with a longer length of failure arc. Whereas the soil cohesion and internal friction angle which contributed to the resisting force increased the FS of slope. Higher soil cohesion caused the critical slip surface to be larger and deeper; the length of failure arc also increased. As the soil internal friction angle increased, the critical slip surface became smaller and shallower, and length of failure arc decreased. Minimum FS increased significantly with the Beta, β angle but not much effect was observed for Alpha, α angle. The location and arc length of critical slip surface had not much difference with the increase of Beta, β angle. However, the critical slip surface became larger and deeper, and failure arc length increased when Alpha, α increased. When driving forces overcome resisting forces, the slope is unstable and will result in mass wasting. The dimensionless function λ which is related to γ, c, φ affected the slip surface. However, the slip surface remained unchanged with constant λ, although there was a change of shear strength parameter.